Development and Preliminary Investigation of a Semiautonomous Socially Assistive Robot (SAR) Designed to Elicit Communication, Motor Skills, Emotion, and Visual Regard (Engagement) from Young Children with Complex Cerebral Palsy: A Pilot Comparative Trial. (23rd January 2019) - Clark, Cecilia; Sliker, Levin; Sandstrum, Jim; Burne, Brian; Haggett, Victoria; Bodine, Cathy
Abstract : Through play, typically developing children manipulate objects and interact with peers to establish and develop physical, cognitive, language, and social skills. However, children with complex disabilities and/or developmental delays have limited play experiences, thus compromising the quality of play and acquisition of skills. Assistive technologies have been developed to increase opportunities and level of interaction for children with disabilities to facilitate learning and development. One type of technology, Socially Assistive Robotics, is designed to assist the human user through social interaction while creating measurable growth in learning and rehabilitation. The investigators in this study designed, developed, and validated a semiautonomous Socially Assistive Robot to compare with a switch-adapted toy to determine robot effectiveness in quantity of, changes in, and differences in engagement. After interacting with both systems for three sessions each, five of the eight subjects showed a greater level of positive engagement with the robot than the switch-adapted toy, while the remaining three subjects showed slightly higher positive engagement with the toy. The preliminary results of the study suggest that Socially Assistive Robots specifically designed for children with complex cerebral palsy should be further researched and utilized to enrich play interactions and skill development for this population.